Comparison of ostial versus very wide antral circumferential pulmonary vein isolation using pulsed field ablation. (19th May 2022) - Tilz, R; Heeger, C; Eitel, C; Vogler, J; Phan, L; Feher, M; Keelani, A; Kuck, K; Kirstein, B
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary vein isolation (PVI) is the gold standard for first-time atrial fibrillation (AF) ablation procedures. Wide antral circumferential ablation (WACA) in comparison to ostial PVI has been attributed to an improved rhythm outcome after AF ablation. Pulsed field ablation (PFA) is a novel energy source with promising safety and efficacy advantages over existing ablation methods due to its unique myocardial tissue specificity. Feasibility of PFA for very WACA has not been investigated so far. Objective: To evaluate procedural characteristics and lesion formation during wide antral circumferential PVI in comparison to ostial PVI using a PFA system. Methods: Thirty-seven consecutive AF patients underwent first-time PFA under deep sedation. Patients eighter received ostial (ostial group; N = 15: 66 % paroxysmal AF; age: 69 years; 66 % male) or very wide antral (vWACA group; N = 22: 59 % paroxysmal AF; age: 62 years; 73 % male) PFA. Pre and post ablation LA voltage maps were acquired using a 20-pole spiral catheter together with a 3-dimensional electroanatomic mapping system (voltage cutoff ≤0.5 mV). On post ablation maps, lesion size by encircling the ablated area was measured. In all patients, 8 pulse trains (2kV/2.5 sec, bipolar, biphasic, 4x basket/flower configuration each) were delivered to each pulmonary vein (PV). In the vWACA-group, extra pulse trains in flower configuration were added to each PV in a wide antral position continuous intraluminal esophageal temperatures (TESO) were monitored with an S-shaped esophageal temperature probe. Results: A median of 8 [IQR 8;8] and 10 [IQR 10;11] pulse trains per PV for ostial and vWACA PVI were applied. vWACA PFA resulted in significant larger lesion formation (47.3 cm2 [IQR 39.1; 52.0]) in comparison to ostial PFA (35.5 cm2 [IQR 30.3; 38.1], p=0.013) with consecutive posterior LA wall isolation in 19/22 (86 %) patients (Figure 1). In the vWACA group, median TESO increased by 0.7 °C (TESOmax 36.5 °C [IQR 36.0;36.9]). However, the vWACA approach was not associated with a significant increase in procedure time, sedation dosage or exposure to radiation. Conclusion: Very wide antral circumferential PFA of the PVs is feasible and was associated with significant larger lesion formation in comparison to conventional ostial PFA. Concomitant posterior LA wall isolation occurred in the majority of patient and did not result in a clinically significant increase of intraluminal esophageal temperatures, procedure time, sedation and radiation dosage.